2013
DOI: 10.1089/ten.tec.2012.0452
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Collagen–Hydroxyapatite Composite Fabricated via a Novel Perfusion-Flow Mineralization Technique

Abstract: Prevalent three-dimensional scaffolds for bone tissue engineering are mineralized collagen-hydroxyapatite (Col/HA) composites. Conventional mineralization techniques are either to coat collagen scaffold surfaces with minerals or to simply mix collagen and mineral nanoparticles together. These conventional in vitro collagen mineralization methods are different from the in vivo bone formation process and often result in scaffolds that are not suitable for bone tissue engineering. In this study, a unique perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 37 publications
1
67
0
Order By: Relevance
“…This fact was further corroborated by measuring overall construct porosity using helium pycnometry before and after ECM deposition. 35 It was shown that without ECM the overall porosity of the Co/HA scaffold…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact was further corroborated by measuring overall construct porosity using helium pycnometry before and after ECM deposition. 35 It was shown that without ECM the overall porosity of the Co/HA scaffold…”
Section: Resultsmentioning
confidence: 99%
“…The preparation and properties of the Col/HA scaffolds were described in our previous work. 35 Prior to cell studies, the Col/HA discs were sterilized with ethylene oxide and subsequently prehydrated in media overnight at 37°C. Approximately 1 · 10 5 P.3 MSCs were seeded on top of the scaffolds and incubated for 1 h in a 37°C cell-culture incubator allowing cells to attach.…”
Section: Cell Culture On 3d Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Among these biomaterials, type 1 9 To date, mixing collagen with minerals and mineralizing collagen have been used to modify collagen scaffolds for simulating the composition and microstructure of bone tissue to the greatest extent possible. [10][11][12][13][14][15][16][17] Because HA is a primary mineral component of natural bone and possesses outstanding bioactivity, osteoconductivity, biocompatibility with bone cells, good mechanical properties, and a slow degradation rate in vivo, it has often been the first choice for modifying collagen scaffolds. 10,[18][19][20] Although directly mixing collagen with HA powders in certain proportions can result in collagen scaffolds with compositions similar to those of natural bone tissues, it is difficult to simulate their microstructure and microenvironment via this process.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer-induced liquid precursor (PILP) phase stabilized by PAA exhibits liquid-like properties and is suggested to be drawn into the gaps within collagen fibrils by capillary effects. On crystallization, the collagenous matrix encloses organized assemblies of hydroxyapatite nanoparticles formed on phase transformation [38]. Mineralization of the insoluble matrix of nacre material in the presence of PAA also reports morphologies structurally analogous to the natural biomineral [39].…”
Section: Introductionmentioning
confidence: 96%